SURVIVAL STRATEGY OF FORMER WOMEN MIGRANT WORKERS(CASE STUDY OF FORMER MOWEN MIGRANT WORKERS KALIWEDI CIREBON DISTRICT) - Abdul Hakim (Widyariset, 2011)
The issue of poverty that does not go over and the narrowness of employment encourage rural women of Ujungsemi village to migrate. Being maids, they could raise capital to buy land, build houses and to open the business after returning home. The economic difficulties that had been churned from resolved even more than enough. However, the above condition does not last long. They have to go back and start life at home. The problem of this research: how social and economic conditions of former migrant workers, as well as what strategies they are doing to maintain viability. Field data were obtained by using interview and observation techniques. The data analysis phase is the stage of reduction, display and analysis. Informants are selected using purposive samplingtechnique. This research indicates that the former migrant workers initially had a mass liminality when returning to village that impact on business start work; changes in social and employment status. For maintaining the viability, they make such a strategies, among others, the use of social networks; girls mobilization; minimization of the number of children; saving; production of subsistence and additional income, reduce the cost of living and the utilization of the loan.